GROWTH AND YIELD RESPONSE OF FIELD PEA (PISUM SATIVUM L.) TO GAMMA IRRADIATION STRESS - Majeed, Abdul; Muhammad, Zahir; Ullah, Rehman (Plant Breeding and Seed Science, 2016)
Ionizing radiation has extensive applications in agriculture for inducing mutagenic changes in major field crops, potential breeding purposes, varietal development and crop improvement. This study was conducted to test the efficacy of 0.8, 1.6, 2.4 and 3.6 kGy gamma irradiation doses (Cobalt-60) upon growth and yield performance of edible pea (Pisum sativum L.) in pot culture experiment during 2009. Results demonstrated that higher radiation doses (1.6 and 3.2 kGy) significantly influenced the studied attributes of P. sativum. It was observed that 3.2 kGy had detrimental effects on shoot and pod lengths of pea which were reduced by 14.60 and 17.71 % respectively when compared to control. Differential response of the number of seeds pod-1, 1000 grain weight and dry biomass of pea were recorded at the applied doses. Significant reduction in number of seeds (-14.21 %) but increase in 1000 grain weight (+13.93 %) and dry biomass (+11.32 %) of pea were recorded at 1.6 kGy which revealed stimulatory effects on grain weight and dry biomass. Conversely, radiation dose 3.2 kGy was found detrimental to all the studied parameters except number of pods plant-1 and number of seeds pod-1 which were not affected.